Nutritional influences on headache: mechanisms and implications - Akgor, Merve Ceren; Mohamed, Wael Mohamed Yousef; Bolay, Hayrunnisa (Springer, 2025)
Nutritional factors play a crucial role in the pathophysiology of headache disorders, influencing both the frequency and severity of attacks. Various dietary triggers, including chocolate, citrus fruits, nuts, dairy products, processed foods, and alcohol, have been implicated in headache, with underlying mechanisms involving biogenic amines, neurotransmitter modulation and inflammatory pathways. While histaminergic foods are commonly associated with migraines, emerging evidence suggests that dopaminergic foods may play a role medication overuse headache (MOH). The gut- brain and gut microbiota alterations have gained increasing attention as potential contributors to headache disorders. Studies indicate that individuals with migraine exhibit a higher prevalence of gastrointestinal conditions such as irritable bowel syndrome (IBS), suggesting a bidirectional relationship between gut dysbiosis and headache pathogenesis. Additionally, oxidative stress, mitochondrial dysfunction, and neuroinflammatory processes have been implicated in the dietary modulation of headaches. Understanding the complex interplay between nutrition, metabolic pathways, and neuronal activity is essential for developing effective dietary strategies for headache prevention and management. Future research should focus on personalized nutrition approaches, considering individual dietary sensitivities and gut microbiota profiles to optimize headache treatment strategies.